Perceptions of the Coach–Athlete Relationship Predict the Attainment of Mastery Achievement Goals Six Months Later: A Two-Wave Longitudinal Study among F. A. Premier League Academy Soccer Players - Nicholls, Adam R.; Earle, Keith; Earle, Fiona; Madigan, Daniel J. (Frontiers in Psychology, 2017)
All football teams that compete within the F. A. Premier League possess an academy, whose objective is to produce more and better home-grown players that are capable of playing professionally. These young players spend a large amount of time with their coach, but little is known about player’s perception of the coach-athlete relationship within F.A. Premier League Academies. The objectives of this study were to examine whether perceptions of the coach-athlete relationship changed over six months and if the coach-athlete relationship predicted self-reported goal achievement among F. A. Premier League academy players. This study included cross-sectional (n = 104) and longitudinal (n = 52) assessments, in which academy soccer players completed a measure of the coach-athlete relationship and goal achievement across either one or two time periods. The cross-sectional data were subjected to bivariate correlations, whereas the longitudinal data were analyzed using multiple regressions. Perceptions of the coach-athlete relationship remained stable over time. The coach-athlete relationship predicted the achievement of mastery goals six months later. Enhancing the quality of the coach-athlete relationship among elite adolescent athletes appears to be a suitable way of maximizing mastery achievement goals, particularly among developmental athletes who participate in team sports.